2005
DOI: 10.1088/0957-4484/17/1/007
|View full text |Cite
|
Sign up to set email alerts
|

Patterned anodic aluminium oxide fabricated with a Ta mask

Abstract: Electrochemical anodization was applied to an aluminium (Al) sheet patterned with a metallic tantalum (Ta) mask, which gave rise to the formation of patterned anodic aluminium oxide (AAO). The morphological evolution of the AAO porous structure with anodizing time was characterized by scanning electron microscopy. Lateral anodizing of the Al sheet gradually developed underneath the metallic Ta mask with the increase of anodizing time. This has given us further understanding of the Al anodizing behaviour compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The formation of ordered anodic porous alumina from the aluminum surface covered with a metallic Ta mask was also presented [440].…”
Section: Self-organized and Prepatterned-guided Growth Of Highly Ordementioning
confidence: 99%
See 1 more Smart Citation
“…The formation of ordered anodic porous alumina from the aluminum surface covered with a metallic Ta mask was also presented [440].…”
Section: Self-organized and Prepatterned-guided Growth Of Highly Ordementioning
confidence: 99%
“…During the self-organized anodizing of aluminum, the process of pore nucleation is a combination of random nucleation and nucle- ation at surface faults. Moreover, the grain boundaries and scratches on the aluminum surface are sites for preferential pore development [440]. The pre-treatment process control must be focused on the reduction of surface faults, or on their controlled and reproducible generation, in the required morphology.…”
Section: Aluminum Pre-treatmentmentioning
confidence: 99%
“…It has been reported that the orientation of the nanopore channels in AAO can be directed away from surface normal by putting aluminum in tension parallel to surface. 10 In addition, curved and dendritic pore channels can also be made by controlling the surface topography of aluminum 11,12 or with the aid of a patterned mask. 12 There have been no literature studies on the fabrication of AAO with uniformly aligned nanopore arrays off surface normal.…”
Section: Introductionmentioning
confidence: 99%
“…This state describes a droplet of water that fills the cavities of a rough surface and remains even when the surface is tilted to a high angle to clean the surface. In contrast, according to the Cassie–Baxter approach, a water droplet sits on top of the protuberances and does not fill the cavities, regardless of the roughness 17, 18. For example, water sits on the solid protuberances, whereas air fills the pockets of the rough surface.…”
Section: Introductionmentioning
confidence: 99%